Judging words: the task of criticism. Issue 9 (21st October 2019) - Stables, Wayne
ABSTRACT: Criticism is apt to take the existence of its object for granted. This article's interest is in an attitude that takes criticism to be constitutive of its object rather than secondary to it. After locating this attitude via Hegel, at the threshold between Kantian and Romantic aesthetics, the article shows how Walter Benjamin risks its consequences. Benjamin adopts a stance towards a condition of lapse in or as the object, which is then revealed to be tantamount to the founding condition of the possibility of criticism. Ascribing priority to the object amounts to a disavowal of loss. Consequently, lest criticism become a fetish, it may be necessary for it to lay a foundation on something other than the work as such. Benjamin's reading of Genesis is presented as an exemplary instance of such an approach.